2021
DOI: 10.1186/s12991-021-00355-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of transcranial direct current stimulation and mindfulness-based stress reduction on mental fatigue, quality of life and aggression in mild traumatic brain injury patients: a randomized clinical trial

Abstract: Background The rate of traumatic brain injuries (TBIs) due to the accidents is high around the world. Patients with mild TBIs may suffer from some psychological disorders, including aggression, and mental fatigue, and thus their quality of life decreased. Among different treatments for TBI, two treatments, namely transcranial direct current stimulation (tDCS), and mindfulness-based stress reduction (MBSR) have shown to be effective. Therefore, this study aimed to compare the effects of these tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…For example, a study investigating patients with chronic pelvic pain showed that a single session of anodal tDCS applied to two brain regions, the DLPFC and primary motor cortex, reduced pain and improved quality of life and disability measures ( Divandari et al, 2019 ). tDCS has also been shown to improve TBI-related symptoms ( Kang et al, 2012 ; O'Neil-Pirozzi et al, 2017 ; Shirvani et al, 2021 ). Anodal tDCS applied to the PFC is effective in reducing mental fatigue, increasing the quality of life of mild TBI patients, and improving the working memory of severe TBI patients ( Kang et al, 2012 ; O'Neil-Pirozzi et al, 2017 ; Shirvani et al, 2021 ).…”
Section: Pathophysiology Of Pth and Associated Mechanisms After Tbimentioning
confidence: 99%
“…For example, a study investigating patients with chronic pelvic pain showed that a single session of anodal tDCS applied to two brain regions, the DLPFC and primary motor cortex, reduced pain and improved quality of life and disability measures ( Divandari et al, 2019 ). tDCS has also been shown to improve TBI-related symptoms ( Kang et al, 2012 ; O'Neil-Pirozzi et al, 2017 ; Shirvani et al, 2021 ). Anodal tDCS applied to the PFC is effective in reducing mental fatigue, increasing the quality of life of mild TBI patients, and improving the working memory of severe TBI patients ( Kang et al, 2012 ; O'Neil-Pirozzi et al, 2017 ; Shirvani et al, 2021 ).…”
Section: Pathophysiology Of Pth and Associated Mechanisms After Tbimentioning
confidence: 99%
“…Among 14 parallel-arm studies, six studies (43%) (Acler et al, 2013;Charvet et al, 2018;Forogh et al, 2017;Pilloni et al, 2020;Sharma et al, 2019Sharma et al, , 2020 reported improvement only in the tDCS group, five studies (36%) (De Doncker et al, 2021;Dong et al, 2021;Hanken et al, 2016;Mortezanejad et al, 2020;Shirvani et al, 2021) reported an improvement between the groups, two studies (14%) (Gandiga et al, 2006;Ulrichsen et al, 2022) did not report any improvement in either group, and one study (7%) (Charvet et al, 2018) reported inconclusive results due to inadequate data. All the pre-post studies (Chan et al, 2017;Dobbs et al, 2017;Malik et al, 2016;Padalino et al, 2021;Tecchio et al, 2022;Walton Masters et al, 2020) observed a reduction in the fatigue scores post tDCS, except for one (Dobbs et al, 2018) which did not show any improvement.…”
Section: Change In Fatigue Outcomesmentioning
confidence: 99%
“…(1-2 months) was assessed in only three studies (De Doncker et al, 2021;Dong et al, 2021;Shirvani et al, 2021). The diversity observed among these studies highlights that the precise target region for each neurological condition is still subject to question.…”
Section: Does Tdcs Reduce Fatigue?mentioning
confidence: 99%
See 2 more Smart Citations